Measurement on Modulation Transfer Function Under Different Contrasts - Li Wen-juan; Liang Chuan; Jiang Wei; Wang Chi-zhong (Institute of Advanced Engineering and Science, 2013)
Aiming at the effect of environment to MTF measurement, the MTF measurent at different contrasts is presented. In order to get different contrasts, two integrating spheres are used to illuminate the face and back of the test target uniformly. The target luminance and background luminance of the test target are regulated by luminance control parts conveniently. The MTF measurement system is designed and developed. Many experimental results of show that the luminance differences between the values by the system and those by L88 standard level luminance meter are within ±0.3 cd/m2so that the MTF measurement precision can be ensured. MTFs of Sony camera and Cannon camera at different contrasts are measured. The measurement values imply that MTFs at different contrasts can evaluate the imaging quality fully and objectively. This study provides an effective method to assess the imaging quality of visible imaging systems. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1996